Pengembangan Wisata Halal Pemandian Alam Banyubiru di Kabupaten Pasuruan dalam Meningkatkan Ekonomi Lokal - Rossa Ilma Silfiah; Rofiatul Jannah (Jurnal Ilmu Administrasi Negara ASIAN (Asosiasi Ilmuwan Administrasi Negara), 2023)
Halal tourist destinations are currently the target of many tourists, therefore the Pasuruan Regency government is developing halal tourism in the Banyubiru natural bath located in Sumber Rejo Village, Winongan District, Pasuruan Regency. The development of halal tourism is carried out to further develop a unique and better tourism industry, and benefit the local community's economy. This research was conducted to describe the development of halal tourism in the natural baths of Banyubiru in improving the local community's economy. The research method used is descriptive qualitative research method. Data collection techniques were carried out by field observations, interviews, and documentation. The results of the study show that the development of halal tourism in improving the local community's economy is by developing facilities and infrastructure in Banyu Biru tourism, developing halal tourism in providing new jobs, developing halal tourist attractions. In tourism development will experience the impact of tourism development such as in terms of economic, social and cultural. The supporting factors for tourism development are community participation and a unified community while the inhibiting factors are inadequate road access and public transportation, lack of public awareness and the absence of investors as well as the emergence of similar tourism. The aim of developing halal tourism is also to add new jobs as well as attract many tourists to tour the Banyubiru natural baths.